First record of jellyfish Anomalorhiza shawi Light, 1921 (Cnidaria: Scyphozoa) and its associated organisms in Sabah, Malaysia - Chee, Hoe Chuan; Balu Alagar Venmathi Maran; Tzuen, Kiat Yap; Kai, Ching Cheong; Muhammad Ali Syed Hussein; Ejria Saleh; Shau-Hwai Tan (2020)
The present study describes a first record of the jellyfish Anomalorhiza shawi Light, 1921 from Malaysia. It belongs to the family Lychnorhizidae Haeckel, 1880, order Rhizostomeae Cuvier, 1799 (Cnidaria: Scyphozoa). The specimen was taken from Sepanggar Bay, Kota Kinabalu, off the Universiti Malaysia Sabah (UMS) Jetty by manual collection with a bucket. The size of the bell was 430 mm in diameter with oral arms measuring 290 mm in length including the brown terminal clubs, which differentiates A. shawi from other congeners of the family. Anomalorhiza shawi belongs to the monotypic genus Anomalorhiza, and was first reported from the Philippines, with later reports from Hawaii and Thailand. In addition, A. shawi was found associated with other organisms such as the silver shad, Alepes vari (Cuvier, 1833) (Carangidae), and the crab Charybdis feriata (Linnaeus, 1758) (Portunidae). The association between jellyfish and other organisms have been discussed here. A checklist is provided for the current species of scyphozoan jellyfish reported from Malaysia.